2004
DOI: 10.1021/jp035976n
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Determination of the Harmonic Force Constants in Benzene. 3. The Harmonic Frequencies

Abstract: The aim of this work is to present a full set of 34 empirically determined harmonic force constants F i,k for benzene (in symmetrized Whiffen's coordinates), as well as the corresponding set of 20 harmonic normal mode (NM) frequencies for all four D 6 h isotopomers:  C6H6, C6D6, 13C6H6, 13C6D6. The reliability of the obtained harmonic force constant values is reinforced by their ability to reproduce satisfactorily the experimentally measured fundamental vibrational frequencies of the four D 6 h benzene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The electric hypershielding has dimension V m −1 T −2 ≡ kg −1 m s A in the SI system of units. The calculations were carried out using the following base units: [27] mass m e = 9.10938188×10 and density-functional calculations [29][30][31]. With k CH = 5.547×10 2 N m −1 , and k CC = 6.616×10 2 N m −1 [29], the displacement of H and C nuclei due to the strong external magnetic field produces a change Table IV and the numerical derivatives in Table V …”
Section: Magnitude Of Observable Quantitiesmentioning
confidence: 99%
“…The electric hypershielding has dimension V m −1 T −2 ≡ kg −1 m s A in the SI system of units. The calculations were carried out using the following base units: [27] mass m e = 9.10938188×10 and density-functional calculations [29][30][31]. With k CH = 5.547×10 2 N m −1 , and k CC = 6.616×10 2 N m −1 [29], the displacement of H and C nuclei due to the strong external magnetic field produces a change Table IV and the numerical derivatives in Table V …”
Section: Magnitude Of Observable Quantitiesmentioning
confidence: 99%
“…It was found that, for F 1,6,8 = −0.3, the two levels were at 1591.6 and 1609.7 cm -1 , in very good accord with the experimentally measured frequencies: 34 1591.327 and 1609.518 cm -1 . As already pointed out, to achieve this agreement, we also had to introduce minor changes in the values of some of the harmonic force constants that were established in our previous work . Thus, F 6,6 was changed from 0.671 to 0.660 and F 8.8 was changed from 6.670 to 6.660 (aJ and Angstrom).…”
Section: Analysis Of the ν8 ↔ ν1 + ν6 Fermi Resonance In Benzenementioning
confidence: 92%
“…The conventional notation for the normal mode (NM) whose frequency is 1484 cm -1 in C 6 H 6 is ν 19 . However, this notation is obviously not consistent and leads to some confusion when trying to relate the SM to NM . In fact, in terms of the SM treatment, mode no.…”
Section: Analysis Of the Triple ν20 ↔ ν8 + ν19 ↔ ν1 + ν6 + ν19 Fermi ...mentioning
confidence: 99%
See 2 more Smart Citations